(untitled) (Journal of Rashid Latif Medical College, 2023)
Objective: This study was conducted to evaluate 1) ratio of peoplepracticing self-medication in BZU, Multan; 2) their knowledge abouteffects of self-medication; and 3) views about ways to reduce self medication practices.Methodology: The study conducted was questionnaire based duringDecember 2014. It involved a total of 100 participants of which 50 weremale and 50 were female. Results: The prevalence of self-medication wasfound out to be 75%. 48% of the people stated that self-medication cancause both the death of the person as well as the person can becomeaddicted to the medicine. 39% of the participants think that due to lack ofawareness people get attracted to self-medication; and 53% of the peopletake lack of awareness as the leading cause of increasing self-medicationpractices in Pakistan. 81% people stated that self-medication can bestopped. 52% participants think as media can be used to spread awarenesswhile 15% think that by arranging free camps for the poor, we can reducethe self-medication. While 33% people think that by arranging seminars,we can stop self-medication. Conclusion: The prevalence rate as indicatedby this study was very high so proper measures should be taken to reduceits rate. For this purpose, the help of media, seminars or camps can bearranged.